Competitiveness in Urban Europe: research based, practice led - Marloes Hoogerbrugge (European Regional Science Association (ERSA), 2011)
Metropolitan regions and cities are often coined as the `motors of the economy'. The performance of national economies - and even the EU in general - is increasingly dependent on the cumulative performance of metropolitan regions and/or cities. All around the world, cities are increasingly in competition with one another; interconnected in a network of criss-cross relations between firms and institutions. With respect to urban competitiveness, numerous activities of benchmarking and `best practises' between cities exist. Many policies are based upon these evaluations leading to cherry-picking and the hasty copying of experiences from one specific urban context to another. A deeper understanding of the problems and structural mechanisms behind urban competitiveness is often lacking. This paper aims to analyse the competitiveness of European metropolitan regions via a comparative case study research, defining the main threats and challenges concerning the economic vitality of urban areas. It will be driven by the input of regions and cities with the aim to identify `best' and `bad' practices across Europe. In other words, we will set out the contours of a research framework on economic competitiveness that aims to bridge the gap between academic research and urban practices by means of a policy-driven research agenda. The competitiveness of five European regions will be discussed in more detail: Munich, Warsaw, Madrid, Bucharest and Stockholm. Based on roundtable discussions with stakeholders in these cities, the missing blanks in urban research will be defined. This paper will go beyond the ranking lists based solely on economic productivity figures by discussing cities' competitiveness from an integral perspective. The underlying determinants of competitiveness (e.g. local economic sectoral structure, labour market) will be analysed to create a better understanding of the economic performance of cities. It is the aim of this study to make academic research on urban competitiveness applicable for urban practice by listing knowledge and research questions that are of interest for both researchers as well as urban practitioners.
Keywords: 330